Tumor suppressor protein p53 binds preferentially to supercoiled DNA - Palecek, E; Vlk, D; Stanková, V; Brázda, V; Vojtesek, B; Hupp, T R; Schaper, A; Jovin, T M (Oncogene, 1997)
Wild type human tumor suppressor protein p53 (expressed in insect cells) binds strongly to negatively supercoiled (sc) plasmid DNA at a native superhelix density, as evidenced by electrophoretic retardation of scDNA in agarose gels and imaging by scanning force microscopy (SFM). The binding occurs both in the presence and absence of the p53 consensus sequence. At relatively low p53/DNA ratios, binding of p53 to scDNA results in the appearance of several retarded DNA bands on the gels, similar to a conventional topoisomer ladder generated enzymatically. However, after removal of p53 by deproteination, the original mobility of the scDNA is recovered, indicating that the reduction of torsional stress accompanying p53 binding does not reflect changes in linking number. In DNA samples partially relaxed by topoisomerase I p53 binds preferentially to the scDNA molecules with the largest negative superhelix density. SFM imaging of the p53/scDNA complex reveals a partial or total relaxation of the compact scDNA, the degree of which increases with the number of bound p53 molecules. Competition assays with linear DNA reveal a preference of p53 for scDNA. In addition, scDNA induces dissociation of p53 from a preformed complex with a DNA fragment (474 bp) containing the consensus sequence. We conclude that the affinity of p53 for negatively supercoiled DNA is greater than that for the consensus sequence in linear fragments. However, thermally denatured linearized plasmid DNA is efficient in competing for the binding of p53 to scDNA, although the first retarded band (presumed to contain one bound p53 molecule) is retained in the case of the plasmid containing the consensus sequence. Thus, it appears that interactions involving both the core domain and the C-terminal domain regulate the binding of p53 to scDNA. The above results are not restricted to human p53; the wild type rat p53 protein also results in the retardation of scDNA on agarose gels. The biological implications of the novel DNA binding activities of p53 are discussed.
Keywords: Electrophoresis, Agar Gel; konsenzuální sekvence; Humans; Baculoviridae; elektroforéza v agarovém gelu; Protein Binding; mikroskopie atomárních sil; nádorový supresorový protein p53; krysa rodu Rattus; vazebná místa; lidé; zvířata; Binding Sites; DNA; Consensus Sequence; superhelikální DNA; konformace nukleové kyseliny; vazba proteinů; Rats; Spodoptera; Nucleic Acid Conformation; Animals; DNA, Superhelical; Microscopy, Atomic Force; Tumor Suppressor Protein p53